Authority and Dissent in Jewish Life - Greenspoon, Leonard J. (Leonard Jay) (Book collections on Project MUSE., 2020)
"Throughout the long history of Judaism, many individuals and groups have sought to wield authority on the basis of unique religious, social, familial, military, or political claims. Moving historically from the biblical period to the modern-day State of Israel, Authority and Dissent in Jewish Life discusses a range of those claims to authority from within the Jewish community itself. There is no single paradigm that characterizes these instances. Yet again and again the same causes of disagreement arise: interpretation and application of authoritative texts, appropriate ways to remember and memorialize figures from the past, the extent to which traditional leadership roles should (or should not) change in keeping with new cultural or political contexts, the degree to which long-held beliefs and long-practiced rituals are (or are not) susceptible to modification or abandonment, and the tension members of a Jewish community may feel when their leaders make pronouncements at odds with the political policies of the secular state in which they live. Written accessibly, the essays in this collection examine these phenomena from a wide variety of approaches, genres, and media. They pay close attention to the historical and religious settings of the controversies they analyze, yet also allow for ample reflection on the larger issues of authority and dissent that each occurrence raises"--